Digitally-assisted indoor energy scavenging system for adaptive CMOS image sensor applications - Ting, Alvin Kee Hui (2016)
This aim of this project is to design a Power Converter System, which will detect the voltage from the Photovoltaic cell and select different load to operate based on the voltage. The circuit will be design simulated using Cadence Virtuoso 0.18um process. During the initial of the project, research and understanding of the Buck and Boost converter characteristics and how to utilized MOSFET as a switch so as to design the output circuit. After which, the rest of the circuit can be designed and test. The design of the first stage is for the detection of the input voltage levels, and it will output signals to turn off the system if the voltage is insufficient or activate the system to either Buck or Boost mode. The second stage of the circuit will be generating PWM signal for the MOSFET the turn on or off. The third stage will take in the signal from the first and second stage and determine which MOSFET should be on or off so as to make the output behave in Buck or Boost mode. The output of the system when the voltage is above the nominal voltage of the Photovoltaic cell and the system will operate in Boost mode. When the voltage is between 91% of the nominal value and nominal value, it will run the Buck load at the output and Boost load will be cut off. Lastly, the conclusion and future recommendation have been stated together with the simulation results which will set a few direction for future works.